Essential indicators for measuring site‐based conservation effectiveness in the post‐2020 global biodiversity framework. Issue 4 (4th February 2021) - Geldmann, Jonas; Deguignet, Marine; Balmford, Andrew; Burgess, Neil D.; Dudley, Nigel; Hockings, Marc; Kingston, Naomi; Klimmek, Helen; Lewis, Alanah Hayley; Rahbek, Carsten; Stolton, Sue; Vincent, Claire; et al.
Abstract: Work on the post‐2020 global biodiversity framework is now well advanced and will outline a vision, goals, and targets for the next decade of biodiversity conservation and beyond. For the effectiveness of Protected areas and Other Effective area‐based Conservation Measures, an indicator has been proposed for "areas meeting their documented ecological objectives." However, the Convention on Biological Diversity (CBD) has not identified or agreed on what data should inform this indicator. Here we draw on experiences from the assessment of protected area effectiveness in the CBD's previous strategic plan to provide recommendations on the essential elements related to biodiversity outcomes and management that need to be captured in this updated indicator as well as how this could be done. Our proposed protected area effectiveness indicators include a combination of remotely derived products for all protected areas, combined with data from monitoring of both protected area management and trends in species and ecosystems based on field observations. Additionally, we highlight the need for creating a digital infrastructure to operationalize national‐level data‐capture. We believe these steps are critical and urge the adoption of suitable protected area effectiveness indicators before the post‐2020 framework is agreed in 2021.